1987
DOI: 10.1007/bf01315111
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nitrogen fertilizer form on the plant availability of phosphate from soil, phosphate rock and mono-calcium phosphate

Abstract: words: Sechura phosphate rock, plant-availability of phosphate rock, nitrogen fertilizer/ phosphate rock interactions, phosphate rock dissolution and soil pH Abstract. A glasshouse trial using lettuce as the test crop, and laboratory incubations were used to evaluate the influence of various nitrogen fertilizers on the availability of phosphate from an unfertilized loamy sand soil and from the same soil fertilized with Sechura phosphate rock or monocalcium phosphate. The order in which nitrogen fertilizer form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
13
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 11 publications
8
13
0
Order By: Relevance
“…This trend is line with the observation made by Apthorp et al (1987) who indicated that, increased dissolution of phosphate rock did not occur until acidity, generated by nitrification or sulphur oxidation of the fertilizer materials, had significantly lowered soil reaction. Generally, inorganic fertilizers and other soil amendments increase the total soil nutrients levels.…”
Section: Discussionsupporting
confidence: 78%
“…This trend is line with the observation made by Apthorp et al (1987) who indicated that, increased dissolution of phosphate rock did not occur until acidity, generated by nitrification or sulphur oxidation of the fertilizer materials, had significantly lowered soil reaction. Generally, inorganic fertilizers and other soil amendments increase the total soil nutrients levels.…”
Section: Discussionsupporting
confidence: 78%
“…Several extractants have been used to measure increases in solution P during PR dissolution (Apthorp et al, 1987;Bolan and Hedley, 1989). Numerous studies demonstrated close relationships between Olsen-P and P uptake by plants, but NaHCO 3 extractable P often underestimates PR dissolution (Alloush, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The form of nitrogen (N) supplied can also affect the availability of sparingly soluble P compounds (Apthorp et al 1987;Gahoonia and Nielsen 1992). The effect is attributed to the acidification or alkalization of the rhizosphere soil following assimilation of NH 4 + and NO 3 − , respectively Tang et al 2011;Troelstra et al 1985).…”
Section: Introductionmentioning
confidence: 98%